International Trade and Emissions: An Longitudinal Input-Output Analysis - Vinicius Vale; Fernando Perobelli (European Regional Science Association (ERSA), 2014)
Nowadays, an important debate in the international economies is the problem of greenhouse gas emissions and climate change related. Discussions begin to gain the world with the signature of the Kyoto Protocol (1997), where an international agreement was reached to reduce global emissions. However, in this context of mitigation, many controlling policies are based on reducing domestic emissions of GHG, which ignores, for example, CO2 emissions embodied in international trade. Moreover, given sudden expansion and globalization of world economies, pollution embodied in trade flows becomes important for measurement of responsibilities, because the use of final goods and production inputs that a country need not necessarily produced by itself, leading to a growing concern about the problem of carbon leakage. Thus, many studies have taken into consideration the estimated emissions embodied in international trade through, for example, the input-output analysis. In this context, this paper seeks to make an empirical investigation on the responsibility for emissions and international trade. We use data from WIOD, where the data structure consists of Input-Output Tables for 40 countries (27 EU countries and 13 other selected countries) plus the "Rest of the World" for the period 1995 to 2009. Furthermore, the production side is disaggregated into 35 productive sectors. Finally uses atmospheric emissions of CO2 for the same 40 countries selected and RoW. The overall aim is to measure emissions embodied in international trade and to analyze the interactions in terms of sectors and regional, from such countries. We propose the following specific aims: a) to observe, through CO2 emissions in international trade, if there is a concentration of emissions and if this behavior is maintained over the years (1995-2009), b) measure CO2 emissions embodied in production and consumption, c) measure the CO2 emissions embodied in exports and imports of each country and thus verify if the international trade has been used as a way to reduce emissions by countries, d) construction carbon balance for each country. The methodology used involves input-output techniques for calculating carbon emissions embodied in international trade. Thus, aggregate indicators for different countries are obtained, such as coefficients of intensity of CO2 emissions. Moreover, trade balances global CO2 emissions embodied in international trade are calculated and the major net exporters and net importers of CO2 emissions in the world economy are identified. Moreover, these indicators represent the empirical basis for the discussion on the responsibility for emissions, being possible, for example, to make a discussion of responsibilities between producer and consumer countries for environmental impacts. Finally, Miyazawa multipliers are calculated, a methodology that approach the issues of feedback loop between countries, through the decomposition of the Leontief inverse matrix in sub-matrices.
Keywords: C67; D57; Q53; Q54; Q56; 330; CO2 emissions; International trade; Multi-regional input-output model